Self-care Behavior of Hypertensive Patients at Grok-Khi-Noo Tambon Health Promotion Hospital, Mueang District, Buri Ram Province - Suntiwong, Chanathib; Pabpayon, Kanpana; Choojan, Saowanee (Journal of The Royal Thai Army Nurses, 2022)
This descriptive research aimed to study self-care behaviors of hypertension patients and to compare differences between biosocial factors, predisposing factors, enabling factors, reinforcing factors and self-care behaviors of the patients. The sample was hypertension patients who were diagnosed by physician and who were visited Grok-Khi-Noo Tambon Health Promotion Hospital in Buriram Province. The 225 patients were randomized by using simple random sampling method. The research tool was a questionnaire, which was examined for content validity and analyzed for confidence. Data were analyzed by using statistics, percentage, independent t-test and One-Way Analysis of Variance (ANOVA). From the result of this research, it was found that the patients with hypertension had a good level of the proper self-care behaviors and it was found that the patients with different social reinforcing factors had different self-care behaviors with statistical significant difference (p<.05) while the patients with different biosocial factors, predisposing factors, enabling factors did not make any difference.